2022
DOI: 10.1155/2022/4181658
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Mucin Family Proteins in Non-Small-Cell Lung Cancer and its Role in Evaluation of Prognosis

Abstract: Lung cancer is still the major contributor to cancer-related mortality. Over 85% of patients suffer from non-small-cell lung cancer (NSCLC). Mucins (MUCs) are large glycoproteins secreted or membrane-bound produced by epithelial cells in normal and malignant tissues. They are the major components of the mucous gel that covers the surface of the respiratory epithelium. Certain MUCs have been used or proposed to act as biomarkers for lung cancer. Nevertheless, the expression, messenger ribonucleic acid (mRNA) le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…MUC1 is a transmembrane glycoprotein that is aberrantly glycosylated and overexpressed in a variety of epithelial cancers. Previous studies have confirmed that MUC1 is overexpressed in NSCLC tissues [ 75 , 76 ], and in about 70% of ovarian cancer [ 77 ]. Tumor-associated MUC1 (tMUC1) is different from the MUC1 expressed in normal cells and can be used as a biomarker and therapeutic target of cancer [ 78 ].…”
Section: Car T-cell Therapy In Solid Tumorsmentioning
confidence: 87%
“…MUC1 is a transmembrane glycoprotein that is aberrantly glycosylated and overexpressed in a variety of epithelial cancers. Previous studies have confirmed that MUC1 is overexpressed in NSCLC tissues [ 75 , 76 ], and in about 70% of ovarian cancer [ 77 ]. Tumor-associated MUC1 (tMUC1) is different from the MUC1 expressed in normal cells and can be used as a biomarker and therapeutic target of cancer [ 78 ].…”
Section: Car T-cell Therapy In Solid Tumorsmentioning
confidence: 87%
“…Mucins have recently received significant attention as potential biomarkers. Primarily, mucins have become increasingly recognized as valuable biomarkers in a wide spectrum of cancers, including lung cancer [42][43][44][45][46][47][48][49][50][51][52]. Therefore, mucins present potential molecular targets for cancer therapy [53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…The MUC gene family, CLDN gene family, and ZNF gene family were among the regulated genes selected for univariate COX analysis, based on previous reports [ [19] , [20] , [21] ]. Following this, the R package “ConsensusClusterPlus” [ 22 ] was used to perform consensus clustering of the subtypes within the cohort.…”
Section: Methodsmentioning
confidence: 99%